Composition of the essential oil of cistus parviflorus L. From Turkey - (:unkn) unknown (My University, 2004)
Water distilled essential oil of Cistus parviflorus L. From Turkey was analyzed by GC/MS. Seventy-six representing 89.4% of the oil were identified. 8-α-13-oxy-14-ene-epilabdane (18.2%), manoyl oxide (9.1%) and δ-cadinene (6%) were characterized as major constituents. © 2004, Taylor & Francis Group, LLC. All rights reserved.
Keywords: 8-α-13-oxy-14-ene-epilabdane; Cistaceae; Cistus parviflorus; Essential oil composition; Manoyl oxide